2022
DOI: 10.1097/prs.0000000000009982
|View full text |Cite
|
Sign up to set email alerts
|

“Alpha Defensin-1 Biomarker Outperforms Culture in Diagnosing Breast Implant-Related Infection: Results from a Multicenter Prospective Study.”

Abstract: Background: Prompt diagnosis of breast implant infection is critical to reducing morbidity. A high incidence of false-negative microbial culture mandates superior testing modalities. Alpha defensin-1 (AD-1), an infection biomarker, has outperformed culture in diagnosing periprosthetic joint infection with sensitivity/specificity of 97%. After previously demonstrating its feasibility in breast implant-related infection (BIRI), this case-control study compares the accuracy of AD-1 to microbial culture in suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In fact, AD-1 has become a critical component in the diagnosis of prosthetic joint infection following orthopaedic intervention, as it is routinely found within infected periimplant uid collections and remains uniquely unchanged in the setting of indolent infections or previous antibiotic exposure [9][10][11][12]. Its use in the diagnosis of breast implant-associated infection remains limited; however, in a previous study performed by our group, we demonstrated superior sensitivity and speci city of AD-1 in the identi cation of peri-prosthetic breast infection when compared to standard bacterial culture [13,14].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In fact, AD-1 has become a critical component in the diagnosis of prosthetic joint infection following orthopaedic intervention, as it is routinely found within infected periimplant uid collections and remains uniquely unchanged in the setting of indolent infections or previous antibiotic exposure [9][10][11][12]. Its use in the diagnosis of breast implant-associated infection remains limited; however, in a previous study performed by our group, we demonstrated superior sensitivity and speci city of AD-1 in the identi cation of peri-prosthetic breast infection when compared to standard bacterial culture [13,14].…”
Section: Introductionmentioning
confidence: 80%
“…Whereas AD-1 stands to supplant bacterial culture as a point-of-care resource to identify peri-prosthetic infection, there remains a gap in our ability to differentiate between mild, moderate, and severe infections with current diagnostic tools [8,13]. It stands to reason that relative AD-1 concentrations within uid samples may serve as a surrogate marker for the extent of pathogenic metabolic activity and innate in ammatory response, thereby demonstrating utility as a marker of infection severity.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Whereas AD-1 stands to supplant bacterial culture as a point-of-care resource to identify periprosthetic infection, there remains a gap in our ability to differentiate between mild, moderate, and severe infections with current diagnostic tools. 8,13 It stands to reason that relative AD-1 concentrations within fluid samples may serve as a surrogate marker for the extent of pathogenic metabolic activity and innate inflammatory response, thereby demonstrating utility as a marker of infection severity. The aim of this study is to evaluate the relationship between quantitative AD-1 levels and infection severity in patients who present with suspected periprosthetic infection.…”
Section: Introductionmentioning
confidence: 99%
“…9–12 Its use in the diagnosis of breast implant-associated infection remains limited; however, in two prior studies performed by our group, we demonstrated superior sensitivity and specificity of AD-1 in the identification of periprosthetic breast infection when compared with standard bacterial culture or Gram stain. 13,14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation